Is an Intra-Islamic Theological Ecumenism Possible? A Response to Sherman Jackson - Atif Khalil (International Institute of Islamic Thought, 2005)
It is rare to find within contemporary Islamic thought writers who are conversant in both the classical Islamic theological heritage and recent developments in philosophy and theology. More often than not, those who do attempt to engage in Islamic theology display either an ignorance of the past or the present. This is not, however, the case with Sherman Jackson, who joins a small handful of others, such as S. H. Nasr, Khalid Abou Fadl, and Abdal Hakim Murad, whose works – diverse as they are – reflect a grasp of both the Muslim intellectual tradition and modern thought. Jackson’s recent On the Boundaries of Theological Tolerance in Islam (Karachi: Oxford University Press, 2002) is not only a translation of al- Ghazali’s Faysal al-Tafriqah bayna al-Islam wa al-Zandaqah (The Decisive Criterion for Distinguishing Islam from Masked Infidelity), one of the most significant medieval attempts to formulate a method to definitively delineate “orthodoxy,” but is prefaced by a highly original essay in which, among other things, he ventures to extend al-Ghazali’s project by redefining and expanding the limits of Islamic orthodoxy within a contemporary context. In this sense, the introduction is a creative and laudable attempt by a serious Muslim thinker to do Islamic theology rather than merely exposit the dogmatic formulations of his medieval predecessors. As such, the introductory essay is the most original part of the book,1 since it is here that Jackson argues, among other things, for the possibility of an intra-Islamic theological ecumenism, one in which creedal schools that previously saw each other as misguided might come to a greater recognition of their mutual legitimacies. This is, indeed, an ambitious project. Yet, few of the book’s reviewers seem to have fully appreciated the magnitude of Jackson’s project as laid out in his introductory essay – virtually an independent piece in its own right – and devoted, instead, the bulk of their reviews to the rest of the work.2 What I intend to do in the few pages that follow is to respond briefly to some of his arguments insofar as they pertain to his ideas on intra-Islamic theological ecumenism.3 My purpose is to show that despite the ingenuity with which he tackles the issue of doctrinal and theological diversity, many of his central arguments are beset by internal contradictions and incongruencies that might otherwise evade the casual reader ...